toolis: A note-taking application with the integration of optical character recognition / Nurul Fadhilah Hanim Mohd Fauzi - Mohd Fauzi, Nurul Fadhilah Hanim (2022)
Toolis: A Note-Taking Application with the Integration of Optical Character Recognition is a mobile application that is used by users for note-taking or transcribing activities. Note-taking is an activity that occurs often in a person’s day-to-day activities. From writing down ideas, scribbling phone numbers, listing down groceries list and making plans, note-taking is an activity that requires a great cognitive load of a person. Usually, to overcome the cognitively demanding task of taking down notes, a person has to limit their note-taking to solely either comprehension or transcription. To do both of those activities simultaneously will certainly put a great pressure on a person’s memory load. Hence, the optical character recognition integrated into this application aims to lessen the cognitive load and pressure of a person during the note-taking activity. Parallelly, the project aims to evaluate the usability of the optical character recognition feature in day-to-day operations. During the development of the project, the System Development Life Cycle (SDLC) using the Agile model is served as the development methodology. On the other hand, the chosen methodology for the development of the application is the Mobile Application Development Life Cycle (MADLC). To evaluate all the usability and all the features included in the application, Alpha testing has been carried out. The testers were given eleven tasks to execute and the outcome of those tasks are determined by the options ‘pass’ or ‘fail’. Based on the results, it can be concluded that all the tasks were able to be executed successfully.